Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

On the wind-driven European shelf sea-level variability and the associated oceanic circulation - Sam T. Diabaté; Neil J. Fraser; Martin White; Barbara Berx; Louis Marié; Gerard D. McCarthy (Continental Shelf Research, 2025)

Faecal microbial profiles of Angus beef cattle with divergent immune responses - Brianna N. Maslen; Brad C. Hine; Christian Duff; Pamela A. Alexandre; Sam A. Clark; Julius van der Werf; Jason D. White; Sameer D. Pant (Livestock Science, 2025)

Recognising and Protecting the National Benefit of Sustainable Fisheries in the UK - Sarah Coulthard; Ainsley Hatt; Phoebe Lewis; Bryce D. Stewart; Michael Roach; Robert Clark; Sam Fanshawe; Carole Sandrine White; Julie Urquhart; Jerry Percy; Tim Gray; Emily Bulled; et al. (Fish and Fisheries, 2025)
Sustainable commercial fishing makes valuable contributions to coastal regions and broader national benefits. This paper offers three arguments in relation to what is required for the societal benefits of sustainable fisheries to be fully realised and considers each in the context of the UK but with global relevance. First, there is a need to raise the profile of the full range of benefits that are delivered through sustainable fisheries to coastal communities and the broader public. In the UK, the delivery of a ‘national benefit’ objective through fisheries is now enshrined in law by the Fisheries Act, 2020; we operationalise this through a new framing that distils eight ‘national benefits’ that all sustainable fisheries should deliver. Second, better acknowledgement of what society gains from sustainable fisheries must be paralleled with recognition of what society is simultaneously at risk of losing through the decline of the fishing fleet. We detail this decline in a new analysis of long‐term UK data, which highlights that the decline is unequally felt, with some regions of the UK, and small‐scale fishing sectors, experiencing loss more acutely. This reality leads us to argue a third point, that if society is to retain and truly harness the benefits that flow from sustainable fisheries, governing bodies must act quickly to ensure that fisheries are environmentally sustainable, diverse and inclusive, pursuing fisheries that ‘leave no one behind’.

Climate, peace, and conflict—past and present: Bridging insights from historical sciences and contemporary research - Sam White; Dominik Collet; Agustí Alcoberro; Mariano Barriendos; Rudolf Brázdil; Pau Castell; Siyu Chen; Cedric de Coning; Dagomar Degroot; Lukáš Dolák; Stefan Döring; Santiago Gorostiza; et al. (Ambio, 2025)
Concern has risen that current global warming and more frequent extreme events such as droughts and floods will increase conflict around the world. This concern has spurred both social science research on contemporary climate, peace, and conflict as well as research in the historical sciences on past climate, weather, warfare, and violence. This perspectives article compares these two fields of scholarship and examines how each may benefit the other. It finds significant convergences in methods and insights across contemporary and historical research as well as persistent patterns in causal pathways between climate and conflict. Contemporary climate, peace, and conflict (CPC) research may sharpen methods and causal models for historical researchers. Historical studies, particularly those informed by contemporary research, may elucidate deep origins and long-term effects of climate-related conflicts. For policymakers and the public, history offers comprehensible ways to make sense of complex and contingent linkages and to construct cogent narratives of the past as well as storylines for the future.

Current state of plant conservation translocations across Europe: motivations, challenges and outcomes - Sandrine Godefroid; Sam Lacquaye; Andreas Ensslin; Sarah Dalrymple; Thomas Abeli; Hannah Branwood; Inmaculada Ferrando Pardo; P. Pablo Ferrer Gallego; Elke Zippel; Luísa Gouveia; Carlos Alberto Lobo; Francisco Fernandes; et al. (Biodiversity and Conservation, 2025)

A transdisciplinary model for teaching and learning for sustainability science in a rapidly warming world - Orla Kelly; Peta White; Fabrizio Butera; Sam Illingworth; Pim Martens; Maud Huynen; Susan Bailey; Geertje Schuitema; Sian Cowman (Sustainability Science, 2023)

Molecular characterisation of the Australian and New Zealand livestock Chlamydia pecorum strains confirms novel but clonal ST23 in association with ovine foetal loss - Martina Jelocnik; Rhys T. White; Tom Clune; John O’Connell; Jonathan Foxwell; Sam Hair; Shane Besier; La Tom; Nyree Phillips; Amy Robbins; Daniel Bogema; Paola K. Vaz; et al. (Veterinary Microbiology, 2023)

Societal impacts of historical droughts in a warming world - Nicolas Maughan; Chantal Camenisch; Rudolf Brázdil; Sam White (Regional Environmental Change, 2022)

Fine root dynamics across pantropical rainforest ecosystems - Walter Huaraca Huasco; Terhi Riutta; Cécile A. J. Girardin; Fernando Hancco Pacha; Beisit L. Puma Vilca; Sam Moore; Sami W. Rifai; Jhon del Aguila‐Pasquel; Alejandro Araujo Murakami; Renata Freitag; Alexandra C. Morel; Sheleme Demissie; et al. (Global Change Biology, 2021)
Fine roots constitute a significant component of the net primary productivity (NPP) of forest ecosystems but are much less studied than aboveground NPP. Comparisons across sites and regions are also hampered by inconsistent methodologies, especially in tropical areas. Here, we present a novel dataset of fine root biomass, productivity, residence time, and allocation in tropical old‐growth rainforest sites worldwide, measured using consistent methods, and examine how these variables are related to consistently determined soil and climatic characteristics. Our pantropical dataset spans intensive monitoring plots in lowland (wet, semi‐deciduous, and deciduous) and montane tropical forests in South America, Africa, and Southeast Asia ( n = 47). Large spatial variation in fine root dynamics was observed across montane and lowland forest types. In lowland forests, we found a strong positive linear relationship between fine root productivity and sand content, this relationship was even stronger when we considered the fractional allocation of total NPP to fine roots, demonstrating that understanding allocation adds explanatory power to understanding fine root productivity and total NPP. Fine root residence time was a function of multiple factors: soil sand content, soil pH, and maximum water deficit, with longest residence times in acidic, sandy, and water‐stressed soils. In tropical montane forests, on the other hand, a different set of relationships prevailed, highlighting the very different nature of montane and lowland forest biomes. Root productivity was a strong positive linear function of mean annual temperature, root residence time was a strong positive function of soil nitrogen content in montane forests, and lastly decreasing soil P content increased allocation of productivity to fine roots. In contrast to the lowlands, environmental conditions were a better predictor for fine root productivity than for fractional allocation of total NPP to fine roots, suggesting that root productivity is a particularly strong driver of NPP allocation in tropical mountain regions.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Lessons from the past, policies for the future: resilience and sustainability in past crises - John Haldon; Merle Eisenberg; Lee Mordechai; Adam Izdebski; Sam White (Environment Systems and Decisions, 2020)

Occurrence of pathogens in Pacific lamprey (Entosphenus tridentatus) - Aaron D. Jackson; Mary L. Moser; Sam T. Onjukka; Scott LaPatra; Kenneth M. Lujan; Corie Samson; Melissa G. White; Marilyn Blair; Linda Rhodes; Ralph Lampman; Alexa N. Maine; Jeffrey C. Jolley (Reviews in Fish Biology and Fisheries, 2019)

Plant diversity and density predict belowground diversity and function in an early successional alpine ecosystem - Dorota L. Porazinska; Emily C. Farrer; Marko J. Spasojevic; Clifton P. Bueno de Mesquita; Sam A. Sartwell; Jane G. Smith; Caitlin T. White; Andrew J. King; Katharine N. Suding; Steve K. Schmidt (Ecology, 2018)
Despite decades of interest, few studies have provided evidence supporting theoretical expectations for coupled relationships between aboveground and belowground diversity and ecosystem functioning in non‐manipulated natural ecosystems. We characterized plant species richness and density, soil bacterial, fungal and eukaryotic species richness and phylogenetic diversity (using 16S, ITS , and 18S gene sequencing), and ecosystem function (levels of soil C and N, and rates of microbial enzyme activities) along a natural gradient in plant richness and density in high‐elevation, C‐deficient soils to examine the coupling between above‐ and belowground systems. Overall, we observed a strong positive relationship between aboveground (plant richness and density) and belowground (bacteria, fungi, and non‐fungal eukaryotes) richness. In addition to the correlations between plants and soil communities, C and N pools, and rates of enzyme activities increased as plant and soil communities became richer and more diverse. Our results suggest that the theoretically expected positive correlation between above‐ and belowground communities does exist in natural systems, but may be undetectable in late successional ecosystems due to the buildup of legacy organic matter that results in extremely complex belowground communities. In contrast, microbial communities in early successional systems, such as the system described here, are more directly dependent on contemporary inputs from plants and therefore are strongly correlated with plant diversity and density.

CO‐VARIATION IN THE PROBABILITIES OF SIGHTING HARBOR PORPOISES AND BOTTLENOSE DOLPHINS - Paul Thompson; Sam White; Ellie Dickson (Marine Mammal Science, 2004)